2010
DOI: 10.2143/ast.40.1.2049230
|View full text |Cite
|
Sign up to set email alerts
|

On the Upcrossing and Downcrossing Probabilities of a Dual Risk Model With Phase-Type Gains

Abstract: In this paper, we consider the dual of the classical Cramér-Lundberg model when gains follow a phase-type distribution. By using the property of phase-type distribution, two pairs of upcrossing and downcrossing barrier probabilities are derived. Explicit formulas for the expected total discounted dividends until ruin and the Laplace transform of the time of ruin under a variety of dividend strategies can then be obtained without the use of Laplace transforms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 15 publications
0
14
0
1
Order By: Relevance
“…Besides, Avanzi et al (2007) found solutions for equation (2.5) when exponential or mixtures of exponential gains size distributions are considered. Ng (2010) shows solutions when individual gains are phasetype distributed. For higher moments of discounted dividends, Cheung and Drekic (2008) with a similar procedure show integro-differential equations similar to (2.5), for n = 1, 2, ...,…”
Section: Paper Review and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, Avanzi et al (2007) found solutions for equation (2.5) when exponential or mixtures of exponential gains size distributions are considered. Ng (2010) shows solutions when individual gains are phasetype distributed. For higher moments of discounted dividends, Cheung and Drekic (2008) with a similar procedure show integro-differential equations similar to (2.5), for n = 1, 2, ...,…”
Section: Paper Review and Resultsmentioning
confidence: 99%
“…Higher moments have also been considered. See Avanzi et al (2007), Avanzi and Gerber (2008), Cheung and Drekic (2008), Gerber and Smith (2008), Ng (2009) and Ng (2010). Yang and Zhu (2008) compute bounds for the ruin probability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two-layer (a, b) strategy was first considered by Ng (2010), who investigated the present value of dividends under a combined threshold and barrier strategy for the compound Poisson dual model, although the issue of optimality was not considered. This is also related to the multilayer dividend strategy (see, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Under such framework, Ng [18] combined barrier strategy and threshold strategy for the first time and then proposed a hybrid dividend strategy, who considered a dual risk model with phase-type gains under a hybrid dividend strategy and derived the explicit formula for the expected total discounted dividends until ruin and the Laplace transform of the time of ruin. In this paper, we consider the hybrid dividend strategy for the classical risk model.…”
Section: Introductionmentioning
confidence: 99%